The Effect of Halal Label on Product Packaging on Muslim Consumer Purchase Decision - Sultan Nanta Setia Dien Labolo; Alfansyuri Nurul Arsyi; Novita Khairani (Islamic Business and Management Journal, 2023)
The halal label is an important thing in society, especially for Indonesian people, the majority of whose population adheres to Islam. Researchers found that there are several food products consumed by Muslims that have not included a halal label. Mini Market Latansa Gontor 5 of the 100 products sold 20 of them have not been labelled halal, which means 20% do not have a halal label. The methodology that researchers use is quantitative which is a field survey by taking a sample of 130 teachers of Pondok Modern Darussalam Gontor 5 Magelang. The purpose of this study was to determine whether there is an influence and how much influence the halal label has on the interest in purchasing food products at Mini Market Latansa Gontor 5. The data obtained is then processed using the IBM SPSS v.21 application. The results obtained are, of the 20 statements with an error rate of 5%, rCount is greater than rTable with a value level of 0.159, meaning that all statements are valid. The reliability test obtained a Cronbach alpha value of 78.9% for questionnaire X (halal label) and 88.3% for questionnaire Y (consumer purchase interest) greater than 60%, meaning that both questionnaires are reliable. From the results of the simple linear regression test, the probability number is 0.000, which is smaller than 0.5, meaning that there is a significant relationship between X (halal label) and Y (consumer purchase interest). From the results of the T test, it is obtained that the Thitung amount of the level of influence of halal labelling on purchasing interest is 11.398 greater than 1.97838, meaning that variable X has a real influence on variable Y. From the results of the detirminization coefficient test (R2), the result is 0.504, meaning that the level of influence of variable X (halal label) on variable Y (consumer purchase interest) is 50.4%, while the remaining 49.6% is influenced by other factors not examined in this study.